Protective effect of delta opioid receptor agonist (D-Ala2, D-Leu5) enkephalin on permanent focal cerebral ischemia in rats. Issue 10 (6th July 2016) - Fu, Danyun; Liu, Haitong; Zhu, Hui; Li, Shitong; Yao, Junyan
Abstract : To investigate the effect of delta opioid receptor agonist (D-Ala 2, D-Leu 5 ) enkephalin (DADLE) on the permanent focal cerebral ischemia in rats. Thirty four male Sprague–Dawley rats were assigned randomly into three groups: sham group (group Sham, n =10), artificial cerebrospinal fluid group (group ACSF, n =12), and DADLE group (group DADLE, n =12). Permanent middle cerebral artery occlusion was performed to induce permanent focal cerebral ischemia in rats. Then, the animals in group DADLE and group ACSF were treated with DADLE or ACSF by an intracerebroventricular injection at 45 min after ischemia. Neurologic deficit scores were assessed according to the Garcia criterion at 24 h after ischemia. Infarct volume was determined using the 2, 3, 5-triphenyltetrazolium chloride staining method. The histological analysis was used to evaluate the extent of cerebral injury. Compared with the control group, the Garcia scores were significantly higher ( P =0.000) and the infarct volumes ( P =0.018) were significantly smaller in the DADLE treatment group at 24 h after ischemia. These neurologic changes were closely correlated with the outcome of the infarct volumes. In addition, the histological examination showed more intact neurons in rats treated with DADLE than those treated with ACSF at 24 h after ischemia ( P =0.000). DADLE by intracerebroventricular administration at 45 min after ischemia can improve neurologic outcome and mitigate cortical neuronal injury induced by permanent focal cerebral ischemia in rats.